Naskah Kuno Kabuyutan Ciburuy dalam Perspektif Historiografi Indonesia - Saputra Adiguna, Richad; Risa Mustafa, Hanif (Siginjai: Jurnal Sejarah, 2023)
Indonesian historiography is considered to be disoriented in its writing. Instead of building an Indonesiasentrism perspective, it is trapped in colonial historiography. This is due to the lack of diversity of themes and limited sources. One of the efforts to diversify themes and enrich sources can be by studying ancient manuscripts or literature. Studying ancient manuscripts as written sources is considered one of the effective ways of learning history. Because from writing sometimes it can be understood how people thought at that time. One place that holds many ancient manuscripts is Kabuyutan Ciburuy. Many studies on Kabuyutan Ciburuy have used the Old Sundanese script as the object of research, focusing on the writing system and style, but ignoring the substance of the past reality in the ancient manuscripts. The method used in this paper is a qualitative research method with a historical approach. Several manuscripts in Kabuyutan Ciburuy have gone through the digitization and language translation stages. These include Sweka Dharma, Kawih Katanian, The Story of Rama Rahwana's Son, and Amanat Galunggung. Ancient manuscripts cannot be separated from mythical content. It is necessary to understand the cultural background of the local community to be studied. So that historical facts are found in the manuscripts. The utilization of the ancient manuscripts of Kabuyutan Ciburuy certainly needs an approach and other auxiliary sciences, in order to be able to distinguish between reality or myth.